2019
DOI: 10.5455/msm.2019.31.40-44
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fatigue and Pain Self- Efficacy on Health-Related Quality of Life Among Patients with Multiple Sclerosis

Abstract: Introduction: Health-related quality of life is a major issue among patients with Multiple sclerosis (MS). Aim: To explore the effect of fatigue and pain self-efficacy on health-related quality of life among patients with MS. Methods: Between March and May 2018, 85 MS patients from a large Hospital of Athens region completed the questionnaires: a) Missoula-VITAS Quality of Life Index-15, which examines 5 dimensions of quality of life, b) Pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There are four forms of MS, the most common of which are relapsing-remitting MS (RRMS, 85%) and primary progressive MS (PPMS, 10%). Symptoms in MS are unpredictable and variable and include fatigue (80% of patients), abnormal sensations (paresthesias, pain, Lhermitte's sign), motor symptoms (weakness, spasticity spasms), visual dysfunction, tremor, gait impairment, brainstem signs (diplopia, dysphagia, internuclear ophthalmoplegia), cognitive abnormalities, and depression symptoms [7,8]. Fatigue is associated with various health problems and is one of the most common signs of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four forms of MS, the most common of which are relapsing-remitting MS (RRMS, 85%) and primary progressive MS (PPMS, 10%). Symptoms in MS are unpredictable and variable and include fatigue (80% of patients), abnormal sensations (paresthesias, pain, Lhermitte's sign), motor symptoms (weakness, spasticity spasms), visual dysfunction, tremor, gait impairment, brainstem signs (diplopia, dysphagia, internuclear ophthalmoplegia), cognitive abnormalities, and depression symptoms [7,8]. Fatigue is associated with various health problems and is one of the most common signs of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…If patients can satisfy their daily needs, managing the various symptoms of the disease and coping well with difficulties in everyday life, they will improve their QoL [13]. Studies have reported that fatigue reduces physical stamina, limits social duties, and interferes with performance of responsibilities at work and at home, substantially impacting the QoL of patients with MS [7]. Social relationships of patients with MS are limited as are their daily activities, because they have to take their medications (cortisone, interferon, or monoclonal antibody) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The higher the score, the better the perceived QoL. The original version was constructed by Byock and Merriman (1998) and has been used in many hospital and health care settings (Adamopoulou et al, 2019;Dimova, Keskinova, Tzekov, & Ginova-Noncheva, 2019). The scale has been translated (Theofilou et al, 2012) and validated in the Greek population by Theofilou, Aroni, Ralli, Gouzou, and Zyga (2013) with Cronbach's α = .74.…”
Section: Methodsmentioning
confidence: 99%
“…MS is known as one of the most important lifechanging diseases because it damages the best periods of people's life and consequently leads to disability [4]. Symptoms and problems of MS, including fatigue, pain, spasm, weakness, visual impairment, imbalance, tremor, impotence, depression, and cognitive problems, are variable and unpredictable [5]. In addition, patients with MS mostly experience several physical and psychological problems affecting their daily activities, family and social life, independence, and individual planning for the future [6,7].…”
Section: Introductionmentioning
confidence: 99%